Evaluation of the cycle threshold values of RT-PCR for SARS-CoV-2 in COVID-19 patients in predicting epidemic dynamics and monitoring surface contamination. Issue 12 (December 2022) - Chen, Yu-Yan; Shen, Xu; Wang, Yong-Jing; Xie, Jia-Wen; Fang, Zan-Xi; Lin, Li-Rong; Yang, Tian-Ci
Abstract: To evaluate the application of cycle threshold (Ct) values of coronavirus disease 2019 (COVID-19) patients in predicting epidemic dynamics and monitoring surface contamination. The Ct value of reverse transcriptase-polymerase chain reaction for SARS‑CoV-2 from COVID-19 patients inbound overseas in Xiamen, China was collected from October 2020 to December 2021, and the correlation of patients' Ct values with epidemic dynamics and surface contamination was evaluated. The results showed that there was an extreme inverse correlation of positivity rate in the current calendar month (ORF1ab,   r  = −0.692,   P  = 0.004; N, r  = −0.629,   P  = 0.012) and the following calendar month (ORF1ab, r  = −0.801,   P  = 0.001; N, r  = −0.620, P  = 0.018) with the median Ct values. Ct value showed better performance for monitoring surface contamination, with the area under the curve value 0.808(95 %CI: 0.748–0.869) for ORF1ab and 0.807(95 %CI:0.746–0.868) for the N gene. The patients' ORF1ab Ct value< 29.09 or N Ct value< 28. 03 were 11.25 times and 10.48 times more likely to result in surface contamination than those with ORF1ab Ct value ≥ 29.09 or N Ct value≥ 28.03 (OR:11. 25, 95 % CI: 5.52–22.35; OR:10.48, 95 % CI:5.29–20.70). Ct values were associated with the positivity rate in the current or following calendar month and predicted the epidemic dynamics. The Ct values can be used as a predictor for monitoring surface contamination to develop public health responses to COVID-19.